Caribbean writers : a bio-bibliographical-critical encyclopedia - Laniak-Herdeck, Margaret; Herdeck, Donald E., 1924-; Lubin, Maurice Alcibiade, 1917- (Three Continents Press, Inc, 1979)
"2,000 authors ( writing in English, French, Spanish, Dutch and various creoles), 15,000 works cited, 100 pages of bibiographies ( general and critical) and 150 illustrations" --Back cover.